Rheological analysis of cemented carbides and Tungsten powders for additive manufacture via laser powder bed fusion technique - Fábio Miranda; Rodrigo Condotta; Nathalia Marina Gonçalves Pereira; Marcelo Otávio dos Santos; Daniel Rodrigues; Suzilene Real Janasi; Fernando dos Santos Ortega; Gilmar Ferreira Batalha (The Journal of Engineering and Exact Sciences)
In Additive Manufacturing (AM) using the Laser Powder Bed Fusion (L-PBF) technique, spherical powders are the most commonly preferred for direct sintering. However, composites such as cemented carbides and heavy alloys often exhibit irregular shapes. Due to the requirement for extremely fine grain size, the cohesive behavior of the particle bed becomes significant, influencing its compressibility and porosity. These physical properties result in powders with coarse textures, which lead to low fluidity and interruptions in material flow within the ducts. This study evaluates the flowability of WC and W refractory materials combined with Co and Ni. Key interparticle properties, including real and bulk density, bulk compressibility and porosity, and granular shear, were analyzed to understand their influence on the deposition layer behavior in the powder bed. These parameters are crucial for understanding the micro-behavior of granular materials and correlating it with their macro-behavior. The rheological aspects of these composite powders are discussed, aiming to establish correlations between the manufacturing process and the resulting properties of their mixtures.